Identifying proteomic profiles as indicators of disease severity in arrhythmogenic cardiomyopathy. (3rd October 2022) - Akdis, D; Tan, G; Wilzeck, V; Costa, S; Gasperetti, A; Matter, C M; Ruschitzka, F; Brunckhorst, C; Akdis, C A; Saguner, A M; Duru, F
Abstract: Introduction: Arrhythmogenic cardiomyopathy (ACM) is an inherited heart muscle disease characterized by progressive fibrofatty replacement of the myocardium and ventricular arrhythmias. Biventricular (BiV) involvement may lead to heart failure. This study aimed to investigate characteristic proteomic patterns in plasma of ACM patients, and correlated them with clinical outcome as well as physical exercise, to assess if key soluble molecules may serve as specific biomarkers for ACM, and whether mechanical stress induced by physical exercise may alter proteomic patterns in ACM patients. Methods: In 38 ACM patients clinical parameters and major adverse cardiovascular events (MACE defined as presence of sustained ventricular tachycardia, ventricular fibrillation, appropriate therapy from implantable cardioverter defibrillator, sudden cardiac death, death related to end-stage heart failure or cardiac transplant) were obtained prospectively during a mean follow-up period of 36 months. All patients received genetic testing using next generation DNA sequencing. Plasma protein expression was analysed using the Proximity Extension Assay (PEA) technology, where a pair of oligonucleotide-labelled antibody probe binds to each targeted protein. In a subgroup of 11 patients blood was drawn immediately before and 3 hours after standardised bicycle exercise testing, and plasma protein expression was compared. Results: 12 patients had ACM with BiV involvement, and 26 patients had isolated right ventricular (RV) involvement. During the follow-up period, 34 patients had a MACE (30% with RV and 14% with BiV). Over 360 proteins were assessed in all ACM patients and compared to 24 healthy controls. The proteomic signature of ACM patients differed significantly compared to controls, and 32 proteins were upregulated in ACM (Figure 1). The proteomic profiles of patients with RV involvement also differed from those with BiV involvement. Most importantly, after exercise, over 40 proteins were upregulated specifically in ACM patients compared to controls, including key pro-inflammatory, adipogenic molecules and also markers of cardiac fibrosis. Conclusion: Our study shows that ACM patients with RV and BiV involvement have different plasma proteomic profiles compared to healthy controls. Furthermore we were able to demonstrate that, specifically in ACM patients, several pro-inflammatory pathways are upregulated after exercise compared to healthy controls, further elucidating the molecular pathways associated with arrhythmogenicity and disease progression and highlighting the key role of physical stress. Our results may enable the identification of potential future biomarkers for diagnosis and risk stratification and may pave the way for personalized patient specific treatments. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Baugarten Foundation ZurichSwiss National Foundation